Old Armenian voiced spirant վ (v) (diachronic and achronic aspects) - Petrosyan, Vardan (Bulletin of Yerevan University B: Philology, 2022)
In the historical-comparative Armenian studies the following prototypes are reconstructed for the Old Armenian վ (v): *ṷ, *u, *p and *ksṷ. As a matter of fact there are two phonemic prototypes, if we take into account that according to the concept accepted by the comparative Indo-European studies the *ṷ and *u are the positional variations of the same phoneme and one sound combination. The quantitative ratio of վ (v) with the upper mentioned prototypes, as well as the genealogical relations of *ṷ/*u with labiodental [v]-s of the other Indo-European languages on one hand, and the corresponding typological equivalents of վ (v) loan words made from old languages (Indo-European and non Indo-European) on the other hand, show that the main prototype of the Armenian վ (v) has been the Indo-European bilabial semi-vowel *ṷ. The relationships of վ (v) with the other prototypes are comparatively later phenomena and are mainly due various phonetic change processes.
Keywords: Voiced spirant; diachronic aspect; semi-vowel; bilabial vocalic consonant; positional variant; typological approach